Fundus Findings in Dengue Fever: A Case Report - Berna Şahan; Sinan Tatlıpınar; Deniz Marangoz; Ferda Çiftçi (Türk Oftalmoloji Dergisi)
Dengue fever is a flavivirus infection transmitted through infected mosquitoes, and is endemic in Southeast Asia, Central and South America, the Pacific, Africa and the Eastern Mediterranean region. A 41-year-old male patient had visual impairment after travelling to Thailand, which is one of the endemic areas. Cotton wool spots were observed on fundus examination. Fundus fluorescein angiography showed minimal vascular leakage from areas near the cotton wool spots and dot hemorrhages in the macula. Dengue fever should be considered in patients with visual complaints who traveled to endemic areas of dengue fever. (Turk J Ophthalmol 2015; 45: 223-225)